Analysis about relevant didactic aspects in training processes for non academic courses (ARQUISUR Revista, 2014)
The paper present some thoughts regarding relevant didactic aspects in training processes about urban and territorial issues non credit courses for qualified students, that is to say for students of various previous skill levels. The object of the research project in which it is included, is to design and materialize processes of professional training for municipal officers with institutional responsibilities to update their knowledge on those issues. The aspects we developed point to specific areas of interest, among which concepts on teaching and learning, professional training processes and its relation with pedagogic tools. The main conceptual lines in urbanism are also stated, as well as the relationship between the proposal with professionalism and the ethic issues.
Keywords: learning; complexity; teaching; teaching–tools / devices; pedagogic mediation